2013
DOI: 10.1002/nbm.2899
|View full text |Cite
|
Sign up to set email alerts
|

Nuts and bolts of chemical exchange saturation transfer MRI

Abstract: Chemical Exchange Saturation Transfer (CEST) has emerged as a novel MRI contrast mechanism that is well suited for molecular imaging studies. This new mechanism can be used to detect small amounts of contrast agent through saturation of rapidly exchanging protons on these agents, allowing a wide range of applications. CEST technology has a number of indispensable features, such as the possibility of simultaneous detection of multiple “colors” of agents and detecting changes in their environment (e.g. pH, metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
287
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(293 citation statements)
references
References 155 publications
(244 reference statements)
2
287
0
Order By: Relevance
“…ADC: apparent diffusion coefficient, CASL: continuous arterial spin labeling, TTC: 2,3,5-triphenyl tetrazolium chloride, Glu: glutamate, Lac: lactate. However, some issues such as a high specific absorption rate (SAR) 17 and susceptibility to magnetic field heterogeneity 18 should be resolved before applying this technique to routine clinical settings.…”
Section: H-mrsi Mrimentioning
confidence: 99%
“…ADC: apparent diffusion coefficient, CASL: continuous arterial spin labeling, TTC: 2,3,5-triphenyl tetrazolium chloride, Glu: glutamate, Lac: lactate. However, some issues such as a high specific absorption rate (SAR) 17 and susceptibility to magnetic field heterogeneity 18 should be resolved before applying this technique to routine clinical settings.…”
Section: H-mrsi Mrimentioning
confidence: 99%
“…This technique can thus detect low-concentration metabolites through the saturation of rapidly exchanging protons on these metabolites [68]. CEST MRI has been explored for assessing glycogen content in perfused liver [69] and to some extent in human skeletal muscle [70].…”
Section: Non-invasive Mr Detection Of Cerebral Glycogenmentioning
confidence: 99%
“…In CEST MRI, different irradiation frequencies of a longer but weaker saturation RF pulse than spin-lock pulse for spin-lock imaging are applied to obtain the socalled Z-spectrum, the signal intensity ratios compared to the unsaturated signal intensity as a function of offset frequency from water. Asymmetric magnetization transfer ratio (MTRasym), the subtraction of the MTR at the opposite offset frequency of labile proton pool and that at the offset frequency, and other parameters can be derived from Z-spectrum analysis (119). Some animal studies have suggested the potentials of CEST MRI for RT applications, for example, the differentiation of brain tumor reoccurrence from radiation induced necrosis (120), and in vivo imaging of glucose uptake and metabolism in tumors (121).…”
Section: Spin-lock and Chemical Exchange Saturation Transfer (Cest) Mrimentioning
confidence: 99%